MAKNA DENOTATIF DALAM SYAIR TARIAN â€œPOMONTEâ€ MASYARAKAT SUKU KAILI DI KOTA PALU - Kalesaran, Eirene E. P.; Kalangi, Leika Maria Victoria; Salea-Warouw, Martha (Kajian Linguistik, 2017)
This research is about the meaning contained in a song in a dance. The research reveals the denotative meaning that exists in the song "Pomonte" in the regional dance originating from Central Sulawesi Province, precisely from the Kaili tribe. This research used qualitative descriptive method. The data collected by interviewing the native speaker who knows this song, and the data analyzing used the method as suggested by Spredley and Sugiono which is data reduction, data display, and data conclusion. The result of this research shows the lingual form from the lyrics andÂ  the denotative meaning in this traditional song, â€œPomonteâ€, Kaili tribe.Key terms: Denotative meaning, local song, â€œPomonteâ€, Kaili tribe.